IBNU THUFAIL AL HAYY BIN YAQHAN (Kehidupan Pemikiran Tentang Filsafatnya) - M. Solihin (Insititut Agama Islam Agus Salim Metro Lampung, 2022)
Thufail philosophical thoughts contained in the story of Ibn Hayy ibn Yaqhan give us a barometer of that nature and it is merely an imagination to seek the truth that comes from revelation must reach some sensory objects specifically to the thoughts that are universal, without teaching and guidance of human reason can know God's creation is by the markings on its inhabitants and try to understand its form to the philosophical thought of Ibn Thufail humans sometimes experience torpor in the story of Hayy Bin Yaqhan can not reveal the arguments in mind that depict keazalian mutalak , qadim, huduts (new) and the like. Then Ibn Thufail eastern philosophers criticize that what has been explained to them it is not given satisfaction thus to achieve the desires of people who ask for satisfaction always imagined. By philosophy and mysticism.